Bicarbonate and Ca2+ Sensing Modulators Activate Photoreceptor ROS-GC1 Synergistically - Duda, Teresa; Pertzev, Alexandre; Makino, Clint L.; Sharma, Rameshwar K. (Frontiers in Molecular Neuroscience, 2016)
Photoreceptor ROS-GC1, a prototype subfamily member of the membrane guanylate cyclase family, is a central component of phototransduction. It is a single transmembrane-spanning protein, composed of modular blocks. In rods, guanylate cyclase activating proteins (GCAPs) 1 and 2 bind to its juxtamembrane domain and the C-terminal extension, respectively, to accelerate cyclic GMP synthesis when Ca2+ levels are low. In cones, the additional expression of the Ca2+-dependent guanylate cyclase activating protein (CD-GCAP) S100B which binds to its C-terminal extension, supports acceleration of cyclic GMP synthesis at high Ca2+ levels. Independent of Ca2+, ROS-GC1 activity is also stimulated directly by bicarbonate binding to the core catalytic domain. Several enticing molecular features of this transduction system are revealed in the present study. In combination, bicarbonate and Ca2+-dependent modulators raised maximal ROS-GC activity to levels that exceeded the sum of their individual effects. The F514S mutation in ROS-GC1 that causes blindness in type 1 Leber’s congenital amaurosis severely reduced basal ROS-GC1 activity. GCAP2 and S100B Ca2+ signaling modes remained functional, while the GCAP1-modulated mode was diminished. Bicarbonate nearly restored basal activity as well as GCAP2- and S100B-stimulated activities of the F514S mutant to normal levels but could not resurrect GCAP1 stimulation. We conclude that GCAP1 and GCAP2 forge distinct pathways through domain-specific modules of ROS-GC1 whereas the S100B and GCAP2 pathways may overlap. The synergistic interlinking of bicarbonate to GCAPs- and S100B-modulated pathways intensifies and tunes the dependence of cyclic GMP synthesis on intracellular Ca2+. Our study challenges the recently proposed GCAP1 and GCAP2 “overlapping” phototransduction model (Peshenko, I.V., Olshevskaya, and Dizhoor, A. M. (2015) J Biol. Chem 290, 6913-6924).